PENERAPAN PROSEDUR AUDIT KAS DAN BANK PT. ABC OLEH KAP TPC - Nanda Adhy Fadhlurrohman (2022)
PT ABC is engaged in manufacturing. The author had the opportunity to audit cash and bank accounts for PT ABC's annual financial statements. One of the most important assets in the financial statements is cash. There are 2 types of cash owned by PT. ABC is cash on hand and cash in bank. The purpose of writing this final report is to find out the steps in planning a cash and bank audit at PT. ABC by KAP Teramihardja, Pradhono & Chandra, To find out evidence of cash and bank audits, and to find out the results of cash and bank audit tests at PT. ABC by KAP Teramihardja, Pradhono & Chandra. In the discussion of this final project, there are 3 parts, namely the stages of audit planning, implementation of field work and the results of cash and bank audits. Based on the audit results, it shows that the cash balance in the cash opname is the same as the lead schedule and general ledger